The Risk of Recurrent Venous Thromboembolism in Carriers and Non-carriers of the G1691A Allele in the Coagulation Factor V Gene and the G20210A Allele in the Prothrombin Gene - Lindmarker, Per; Schulman, Sam; Sten-Linder, Margareta; Wiman, Björn; Egberg, Nils; Johnsson, Hans; and the DURAC Trial Study Group (Thrombosis and Haemostasis, 1999)
The results concerning the risk of recurrent venous thromboembolism (VTE) in carriers of the G1691A mutation in the coagulation factor V gene are not consistent and this risk in carriers of the G20210A polymorphism in the prothrombin gene has hitherto not been reported. We followed 534 patients for 48 months after their first episode of objectively documented VTE. The prevalence of the G1691A allele in 467 (87.5%) of the patients and in 207 controls was 25.3% and 8.2%, respectively, in heterozygote form and 2.4% and 0.5%, respectively, in homozygote form. The adjusted odds ratio (OR) for the first VTE was 4.4 (95% CI 2.6-7.8). The risk of recurrent VTE in heterozygotes was not statistically different from non-carriers (17.8% vs 17.6%), with 85% power to detect a hazard ratio of 2.35. Homozygotes had a significantly increased risk (p = 0.036) of recurrent VTE. The prevalence of the G20210A allele in 456 patients and 207 controls was 6.1% and 1.4%, respectively. The adjusted OR was 4.6 (95% CI 1.6-19.3) for the first VTE in 28 carriers of this polymorphism. The risk of recurrent VTE for these was not statistically different from non-carriers with an OR of 0.9 (95% CI 0.2-2.9).